Effect of elemental nano boron on the transformation and morphology of boron carbide (B4C) powders synthesized from polymeric precursors - Avcioglu, Suna; Kaya, Figen; Kaya, Cengiz (ELSEVIER SCI LTD, 2020)
This paper reports a modified sol-gel approach to synthesize sub-micron sized B4C particles with controlled morphology and without residual phases, such as boron oxide and amorphous carbon. The modification of polymeric gel network by utilization of elemental nano boron particles changed the thermal degradation behaviour of the gel, enhanced the rate of boron carbide transformation and shifted the transformation temperature to lower heat treatment temperature. Mean particle size of transformed B4C is also reduced as a result of elemental boron addition to gel structure. As a result of elemental boron addition, the amount of residual phases greatly reduced. Therefore, first time to date, it is shown that elemental nano boron has an active role in the reduction of boron oxide as an additional reducing agent besides carbon as well as seeding particles, enhancing crystallization of B4C through the ease of transformation process of B-O-C precursors.
Keywords: Boron carbide; Sol-gel; Polymeric processor; Elemental nano boron; Morphology; Particle size; BORIC-ACID; CRYSTALLIZATION KINETICS; CITRIC-ACID; NANOFIBERS; PLATFORM; B2O3(1); ROUTE; Materials Science